2015
DOI: 10.3389/fmicb.2015.00867
|View full text |Cite
|
Sign up to set email alerts
|

Effects of growth stage and fulvic acid on the diversity and dynamics of endophytic bacterial community in Stevia rebaudiana Bertoni leaves

Abstract: The aim of this study was to learn the interactions among the endophytic bacteria, the plant growth, the foliar spray of fulvic acid, and the accumulation of steviol glycosides in the leaves of Stevia rebaudiana. Metagenomic DNA was extracted from the Stevia leaves at different growth stages with or without the fulvic acid treatment; and the diversity of endophytic bacteria in Stevia leaves was estimated by pyrosequencing of 16S rRNA genes. As results, Proteobacteria, Actinobacteria, Bacteroidetes, and Firmicu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 59 publications
1
25
0
Order By: Relevance
“…The microbial communities were profiled by targeting the V4‐V5 hypervariable regions of the 16S rRNA gene (Yu et al . ) using the Illumina MiSeq (250‐bp paired‐end reads) platform at Macrogen Inc. (Seoul, South Korea; http://www.macrogen.com) as described previously (Jiao et al . ).…”
Section: Methodsmentioning
confidence: 99%
“…The microbial communities were profiled by targeting the V4‐V5 hypervariable regions of the 16S rRNA gene (Yu et al . ) using the Illumina MiSeq (250‐bp paired‐end reads) platform at Macrogen Inc. (Seoul, South Korea; http://www.macrogen.com) as described previously (Jiao et al . ).…”
Section: Methodsmentioning
confidence: 99%
“…Soil that harbors an immensely rich pool of bacterial species is the microbial ‘seed bank’ for roots, and its properties may affect plant physiology and root exudation profiles which in turn profoundly influence the structure of the root endosphere microbiome ( Philippot et al, 2013 ). Studies performed on the endosphere microbiome of different plants, using high-throughput amplicon sequencing, have revealed that host plant species ( Shen and Fulthorpe, 2015 ; Ding and Melcher, 2016 ), genotype ( Marques et al, 2015 ; Rodriguez-Blanco et al, 2015 ), plant organ type ( Hameed et al, 2015 ), developmental stage (e.g., seedling or mature plant) ( Ren et al, 2015a ; Yu et al, 2015 ; de Almeida Lopes et al, 2016 ), growing season (e.g., of trees) ( Shen and Fulthorpe, 2015 ; Ding and Melcher, 2016 ), geographical location (field conditions) ( Edwards et al, 2015 ), soil type ( Edwards et al, 2015 ), host plant nutrient status ( Hameed et al, 2015 ), cultivation practice ( Edwards et al, 2015 ) and fertilization ( Rodriguez-Blanco et al, 2015 ) are among the observed factors that significantly influence the plant endosphere microbiome.…”
Section: Determinants Of Microbial Community Assembly In the Endosphementioning
confidence: 99%
“…Thus, the plant may select its internal microbial population toward a specific ecological role to be played in this ecosystem (Hardoim et al, ; da Silva, Armas, Soares, & Ogliari, ). The plant‐related factors known to determine the structure and composition of endophytic communities are the plant genotype, developmental stage, and crop environmental conditions (İnceoğlu, Salles, Overbeek, & Elsas, ; Van Overbeek & Van Elsas, ; Ren, Zhang, Lin, Zhu, & Jia, ; Yu, Yang, Wang, Li, & Yuan, ). Considering phenological aspects of plants, endophytic communities may also respond to seasonal conditions, as their hosts go through different developmental stages with each season.…”
Section: Introductionmentioning
confidence: 99%